THE EFFECT OF AMELIORANTS AND SYNTHETIC FERTILISERS ON THE GROWTH OF SEVERAL VARIETIES OF ONIONS AFFECTED BY SALINITY - Zaka Apdillah; Wan Arfiani Barus; Asritanarni Munar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The study was conducted in Deli Serdang Regency at an altitude of +13 msal, starting in May-August 2024. Demand for shallots is very high, so expansion of shallot cultivation to marginal lands such as saline soils is necessary. The purpose of this study was to examine the effect of ameliorants and synthetic fertilisers on the growth of several shallot varieties. The study used a split split plot design consisting of three factors, namely: First factor (S): S0 (saline soil + topsoil); S1 (saline soil + sawdust compost); S2 (saline soil + sawdust charcoal). The second factor was synthetic fertiliser (P): P1 (0.37 g/polybag (375 kg/ha)); P2 (0.75 g/polybag (750 kg/ha)); P3 (1.125 g/polybag (1,125 kg/ha). The third factor was variety (V): V1 (Bima Brebes); V2 (Batu Ijo); V3 (Sembrani), which was repeated three times. The observation data were analysed using the F test with a 5% DMRT follow-up test. The results showed that the use of the Bima Brebes variety produced the highest percentage of red onion bulb growth potential with a value of 99%, which was significantly different from the Sembrani variety (81%) and not significantly different from the Batu Ijo variety (92%). The Sembrani variety (V3) and the effectiveness of synthetic fertiliser doses can help red onion plants adapt to salinity, either with or without the aid of ameliorants.